2007
DOI: 10.4049/jimmunol.178.1.301
|View full text |Cite
|
Sign up to set email alerts
|

FoxP3+ T Cells Undergo Conventional First Switch to Lymphoid Tissue Homing Receptors in Thymus but Accelerated Second Switch to Nonlymphoid Tissue Homing Receptors in Secondary Lymphoid Tissues

Abstract: Forkhead box P3 (FoxP3)-positive T cells are a specialized T cell subset for immune regulation and tolerance. We investigated the trafficking receptor switches of FoxP3+ T cells in thymus and secondary lymphoid tissues and the functional consequences of these switches in migration. We found that FoxP3+ T cells undergo two discrete developmental switches in trafficking receptors to migrate from primary to secondary and then to nonlymphoid tissues in a manner similar to conventional CD4+ T cells as well as uniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
128
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(134 citation statements)
references
References 63 publications
4
128
2
Order By: Relevance
“…Upon contact with cognate antigen, naive-like Treg become activated and change their homing receptor expression [11,34,38], comparable to what has previously been reported for conventional T cells [39,40]. We describe elsewhere that naive-like Treg harbor a high degree of plasticity for the induction of organselective homing receptors and respond to local factors of the tissue microenvironment [38].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Upon contact with cognate antigen, naive-like Treg become activated and change their homing receptor expression [11,34,38], comparable to what has previously been reported for conventional T cells [39,40]. We describe elsewhere that naive-like Treg harbor a high degree of plasticity for the induction of organselective homing receptors and respond to local factors of the tissue microenvironment [38].…”
Section: Discussionsupporting
confidence: 77%
“…Whereas CCR7-deficient naive-like Treg fail to recirculate through LN, resulting in an almost complete abolishment of their ability to inhibit the proliferation of naive T cells at this site, effector/memory-like Treg from CCR7 -/-mice display an increased accumulation in inflamed sites, which was accompanied by an enhanced suppression of the inflammatory reaction. CCR7 expression was predominantly observed on naive-like Treg [3,5,6,11,[31][32][33][34] and CCR7-expressing CD62L high CD25 + CD4 + Treg were found to be very efficient in preventing the development of autoimmunity [5] or in suppressing graft-versus-host disease [35,36]. It was suggested that Treg recirculation through LN mediated by CCR7 and CD62L is a prerequisite to suppress priming of autoreactive effector cells.…”
Section: Discussionmentioning
confidence: 99%
“…Differential expression of trafficking receptors, including CD62L, has been used to distinguish lymphoid homing T-regulatory cells [21]. The Tregulatory cells identified in follicles and clusters in the current study expressed CD62L, suggesting T-regulatory cell recruitment akin to that of secondary lymph nodes [21,22].…”
Section: Foxp3mentioning
confidence: 60%
“…+ T-cells [20,21]. Differential expression of trafficking receptors, including CD62L, has been used to distinguish lymphoid homing T-regulatory cells [21].…”
Section: Foxp3mentioning
confidence: 99%
“…In addition, the surface levels of each of these markers were unchanged in FuT7 Ϫ / Ϫ mice (unpublished data). Finally, we compared the ability of WT-and FuT7 Ϫ / Ϫ -T reg cells T reg cells up-regulate cutaneous homing receptors after antigen-recognition in the peripheral LNs ( 12,19,20 ), and suggests that T reg cell activity in nonlymphoid tissues may be important for their ability to prevent fatal autoimmunity after transfer into neonatal sf mice.…”
Section: Resultsmentioning
confidence: 99%